And Tango makes three - Richardson, Justin 1963-; Parnell, Peter (Simon & Schuster Books for Young Readers, 2015)
At New York City's Central Park Zoo, two male penguins fall in love and start a family by taking turns sitting on an abandoned egg until it hatches. Based on a true story.